Arturo Toscanini at NBC - Sandrine Khoudja-Coyez (Transposition)
This article presents and analyses various aspects of how the orchestra conductor Arturo Toscanini was represented in the media and perceived during his years under contract with the National Broadcasting Company, from 1937 to 1954. Over the course of this period, NBC helped elevate him to mythic status using mass media advertising techniques to boost his popularity throughout the United States. In reality, behind Toscanini’s collaboration with the American broadcasting network was an artistic, political and economic agenda which served the interests of both parties.